Ethnobotanical study of medicinal plants used by local communities of Damot Woyde District, Wolaita Zone, Southern Ethiopia - MOA MEGERSA; SAMUEL WOLDETSADIK (Smujo International, 2022)
Abstract. Megersa M, Woldetsadik S. 2022. Ethnobotanical study of medicinal plants used by local communities of Damot Woyde District, Wolaita Zone, Southern Ethiopia. Nusantara Bioscience 14: 10-24. Humans have used traditional medicines, mainly of plant origins, to treat diseases. Early humans faced a tremendous challenge when searching for natural products used as medicines. This study reports on an ethnobotanical study that focused on the traditional medicinal plants used by local communities to treat human and livestock diseases. An ethnobotanical study on medicinal plants was conducted from February 2020 to October 2020. That involved semi-structured interviews, field observations, market surveys, and group discussions with informants to document information on the use and management of medicinal plants by the people of Damot Woyde District. Fifty-seven medicinal plant species belonging to 31 families have been collected in the study area inhabitants use that to treat various diseases in humans and livestock. The leading family was Asteraceae which was represented by 7 species (12.3%), followed by Rutaceae (6 species, 10.5%) and Solanaceae (5 species, 9%). Of the 57 medicinal plants collected, 36 (63.2%) were used to treat human ailments only, while 6 (10.5%) plant species were used to treat livestock ailments only, and 15 (26.31%) were used to treat both human and livestock ailments. Herbs constituted the largest number of 22 species (38.6%), followed by shrubs 18 species (31.6%), trees 15 species (26.3%), and climbers 2 species (3.51%). Leaves (31.3%) were the study area's most commonly used plant parts for preparing traditional remedies. Oral administration was the predominant mode of administration, accounting for 71%. Preference ranking analysis revealed Allium sativum L. was the most preferred plant species for treating the common cold. When the direct matrix ranking was analyzed, Croton macrostachyus Hochst. Ex. Del. was the most commonly used medicinal plant for various purposes. Our finding revealed that plant species' use plays a vital role in treating human and animal diseases in Damot Woyde District. Phytochemical and pharmacological tests are recommended mainly on frequently used medicinal plants.